1995
DOI: 10.1084/jem.181.5.1797
|View full text |Cite
|
Sign up to set email alerts
|

Anti-DNA antibodies bind to DNase I.

Abstract: SummaryPolyspecificity is a well-known property of the anti-DNA antibodies produced by autoimmune animals. In our search for antigen targets of anti-DNA antibodies within tissue extracts, we identified a 32-kD polypeptide that was recognized by a large panel of anti-DNA antibodies. Direct sequencing of this protein disclosed its identity with DNase I. 22 monoclonal anti-DNA antibodies bound to DNase I in direct and competitive immunoassays; out of 15 autoantibodies that did not bind DNA, none had the ability t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
33
2
2

Year Published

1996
1996
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 37 publications
2
33
2
2
Order By: Relevance
“…Rat DNase I carries two mutations (E 13 to D and V 67 to I) responsible for the decrease in actin-binding of rat DNase I [3]. Contrary to the findings of Emlen et al [29] and Pucetti et al [30], we were unable to demonstrate any inhibitory or protective effect of anti-DNA antibodies on the reaction of DNase with DNA in agarose gels. Emlen et al [29] have shown that a 35-45 base pair (bp) DNA fragment in SLE sera is protected from DNase digestion and remains bound to antibody, thereby forming a small, DNase-resistant DNA-anti-DNA immune complex.…”
contrasting
confidence: 99%
“…Rat DNase I carries two mutations (E 13 to D and V 67 to I) responsible for the decrease in actin-binding of rat DNase I [3]. Contrary to the findings of Emlen et al [29] and Pucetti et al [30], we were unable to demonstrate any inhibitory or protective effect of anti-DNA antibodies on the reaction of DNase with DNA in agarose gels. Emlen et al [29] have shown that a 35-45 base pair (bp) DNA fragment in SLE sera is protected from DNase digestion and remains bound to antibody, thereby forming a small, DNase-resistant DNA-anti-DNA immune complex.…”
contrasting
confidence: 99%
“…In any event, the formation of anti-DNase antibody in the treated group did not prevent them from doing better than the diluent-treated controls. The absence of any antiDNase antibody in control mice at times when they had high titres of anti-DNA antibody conflicts with the finding of Puccetti et al [35] that many anti-DNA antibodies bind to DNase. Their suggestion that DNase may be the antigen giving rise to anti-DNA certainly does not seem to be the case in NZB//W F 1 mice.…”
Section: Discussionmentioning
confidence: 60%
“…Hence, the deposition probably did not generate high enough Ab concentrations for such inhibition. Alternatively, anti-DNA Abs have been described to cross-react with DNase-I, which could potentially explain inhibition by Abs in solution but not by deposited Abs (41).…”
Section: Discussionmentioning
confidence: 99%